Factors associated with nurses’ knowledge of frailty in older adults: A cross-sectional study - Lei, Lai I; Hsu, Mei Hua Kerry; Dai, Hong Xia; Liu, Ming (Edelweiss Applied Science and Technology, 2026)
To assess frailty knowledge levels among registered nurses in Macao and identify key predictors, a descriptive cross-sectional survey was conducted among 353 registered nurses in Macao. The validated Older People Frailty Knowledge (OPFK) scale measured frailty knowledge. Data were collected online via SurveyMonkey and analyzed using SPSS 26.0. The mean OPFK score was 71.1 ± 10.0 (range, 45–92), indicating moderate-to-high frailty knowledge. Multiple regression showed female gender (β = 0.18, P < 0.01), ≥5 years of clinical experience (β = 0.22, P < 0.001), positive experiences with older adults (β = 0.25, P < 0.001), and intention to live with older adults (β = 0.15, P < 0.05) were significant predictors, explaining 10.2% of variance (adjusted R² = 0.102). Macao nurses have moderate-to-high knowledge of frailty, but gaps in frailty assessment. Integrating targeted assessment training into gerontological nursing education, promoting continuing professional development, and leveraging experiential predictors can enhance geriatric care capacity.